Exercise and Vitamin D Supplementation Modify Spleen Morphology in Lean, but not, in Monosodium-Glutamate-Obese Rats - Zoé Maria Guareschi; Vanessa Marieli Ceglarek; Patrick Fontes Rodrigues; Luiz Pierre Huning; Cintia Festinalli; João Paulo de Arruda Amorim; Sabrina Grassiolli (Journal of Spleen And Liver Research, 2019)
An experimental study examines how exercise and vitamin D supplementation affect spleen morphology in lean versus MSG‑obese rats, discussing immunologic implications.
Keywords: Swimming